Numerical Investigation for the Modeling of the Magnetic Buoyancy Force during the Natural Convection of Air in a Square Enclosure. (27th May 2014) - Song, Kewei; Tagawa, Toshio; Wang, Liang-bi; Ozoe, Hiroyuki
Abstract : Numerical computations are carried out for natural convection of air in a two-dimensional square enclosure under a nonuniform magnetic field and together with the gravity field. The nonuniform magnetic field is supplied by a cubic permanent magnet placed above the enclosure. Two kinds of the expressions for the magnetizing force are considered and compared in the numerical computations. The flow and temperature fields, the magnetizing force field and the Nusselt number for two kinds of magnetizing force expressions are all presented in this paper. The numerical results reveal that the natural convection inside the enclosure does not depend on the types of the expressions for magnetizing force.